A population of proinflammatory T cells coexpresses Î±Î² and Î³Î¿ T cell receptors in mice and humans - Mills, Kingston; Moran, Barry; Hokamp, Karsten (My University, 2020)
T cells are classically recognized as distinct subsets that express αβ or γδ TCRs. We identify a novel population of T cells that coexpress αβ and γδ TCRs in mice and humans. These hybrid αβ-γδ T cells arose in the murine fetal thymus by day 16 of ontogeny, underwent αβ TCR–mediated positive selection into CD4+ or CD8+ thymocytes, and constituted up to 10% of TCRδ+ cells in lymphoid organs. They expressed high levels of IL-1R1 and IL-23R and secreted IFN-γ, IL-17, and GM-CSF in response to canonically restricted peptide antigens or stimulation with IL-1β and IL-23. Hybrid αβ-γδ T cells were transcriptomically distinct from conventional γδ T cells and displayed a hyperinflammatory phenotype enriched for chemokine receptors and homing molecules that facilitate migration to sites of inflammation. These proinflammatory T cells promoted bacterial clearance after infection with Staphylococcus aureus and, by licensing encephalitogenic Th17 cells, played a key role in the development of autoimmune disease in the central nervous system.
PUBLISHED
cited By 1
Keywords: TCRδ+ cells in lymphoid organs; T cells; Autoimmunity; Neuroinflammation; TCRδ+ cells in lymphoid organs; T cells